2023
DOI: 10.1002/anie.202214991
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Generation of Hydrogen Radical (H⋅) with GSH for Photodynamic Therapy

Abstract: As a reactive hydrogen species, the hydrogen radical (H⋅) scarcely sees applications in tumor biological therapy due to the very limited bio‐friendly sources of H⋅. In this work, we report that TAF can act as an organic photosensitizer as well as an efficient photocatalytic H⋅ generator with reduced glutathione (GSH) as a fuel. The photoactivation of TAF leads to cell death in two ways including triple amplification of oxidative stress via ferroptosis‐apoptosis under normoxia and apoptosis through biological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…In addition, PDT can induce hypoxia as oxygen is consumed during irradiation. , Decreased generation of ROS limits damage to cancerous cells. To address this, there is motivation to develop light-triggered compounds that exploit oxygen-independent mechanisms for phototoxicity. In this context, metal complexes such as Ru(II) polypyridyl systems have attracted considerable attention. ,,, Judicious choice of ligand–metal combinations provides access to a variety of excited-state configurations with characteristic photophysical properties and reactivities. Strategies have included photorelease of bulky ligands to reveal phototoxic metals and/or ligands, ,,,,, photocaging of chemotherapeutics and enzyme inhibitors, ,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…In addition, PDT can induce hypoxia as oxygen is consumed during irradiation. , Decreased generation of ROS limits damage to cancerous cells. To address this, there is motivation to develop light-triggered compounds that exploit oxygen-independent mechanisms for phototoxicity. In this context, metal complexes such as Ru(II) polypyridyl systems have attracted considerable attention. ,,, Judicious choice of ligand–metal combinations provides access to a variety of excited-state configurations with characteristic photophysical properties and reactivities. Strategies have included photorelease of bulky ligands to reveal phototoxic metals and/or ligands, ,,,,, photocaging of chemotherapeutics and enzyme inhibitors, ,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…The GPX-mimicking activity of TADI-COF-Fc was assessed using Ellman’s method, based on the highly specific thiol–disulfide exchange reaction between 5,5′-dithiobis­(2-nitrobenzoic acid) (DTNB) and GSH . Following the incubation of GSH with TADI-COF-Fc (200 μg/mL) at 37 °C for 12 h, approximately 85% of GSH was converted into GSSG, as calculated via spectrophotometric analysis at 415 nm of the yellow 5-mercapto-2-nitrobenzoic acid generated by the exchange reaction (Figure E).…”
Section: Results and Discussionmentioning
confidence: 89%
“…The GPX-mimicking activity of TADI-COF-Fc was assessed using Ellman's method, based on the highly specific thiol− disulfide exchange reaction between 5,5′-dithiobis(2-nitrobenzoic acid) (DTNB) and GSH. 92 Following the incubation of GSH with TADI-COF-Fc (200 μg/mL) at 37 °C for 12 h, approximately 85% of GSH was converted into GSSG, as calculated via spectrophotometric analysis at 415 nm of the yellow 5-mercapto-2-nitrobenzoic acid generated by the exchange reaction (Figure 5E). Kinetic tracing unambiguously showed that the reaction rate was dependent on the TADI-COF-Fc concentration, with a good linear relationship between the rate constant and TADI-COF-Fc concentration (Figure 5F, G, and Figure S12).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is urgent to design and tailor catalysts for artificial S−S synthesis based on the oxidative coupling mechanism. Generally, free radicals and related reactive species are considered prioritized green agents for triggering and boosting the oxidative coupling reaction due to their superior activity and efficiency among all the incumbent candidates with oxidizing capacity, 21,22 T h i s c o n t e n t i s ), hydrogen peroxide (H 2 O 2 ), etc. So far, photoinduced free-radical production over semiconductor photocatalysts under mild conditions is an ideal pathway, enabling high radical concentrations, long lifetimes, and precise management of suitable redox chemical potential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, it is urgent to design and tailor catalysts for artificial S–S synthesis based on the oxidative coupling mechanism. Generally, free radicals and related reactive species are considered prioritized green agents for triggering and boosting the oxidative coupling reaction due to their superior activity and efficiency among all the incumbent candidates with oxidizing capacity, , including holes (h + ), superoxide radicals (•O 2 – ), singlet oxygen ( 1 O 2 ), hydroxyl radicals (•OH), sulfate radicals (•SO 4 – ), hydrogen peroxide (H 2 O 2 ), etc.…”
Section: Introductionmentioning
confidence: 99%